Assessment of the compliance, influencing factors, and yielding results of liver cancer screening in a high‐risk population: A cross‐sectional study. Issue 20 (23rd August 2022) - Cao, Maomao; Li, He; Sun, Dianqin; He, Siyi; Yang, Fan; Yan, Xinxin; Zhang, Shaoli; Zha, Zhenqiu; Zhou, Jinyi; Luo, Pengfei; Gong, Jiyong; Ma, Hengmin; et al.
Abstract : Background: The participation and results for liver cancer screening are rarely reported. The aim of this study was to determine the participation rates and factors affecting participation rates as well as to report the detection rate for liver cancer in an organized screening program. Methods: The organized screening program for liver cancer was conducted in 12 rural sites. The risk of developing liver cancer was initially evaluated for each participant. High‐risk individuals were offered α‐fetoprotein measurement and ultrasonography examination. Potential risk factors associated with the participation rate were screened by fitted generalized linear mixed logistic regression models through reporting odds ratios (ORs) with 95% CIs. Results: A total of 358, 662 eligible participants completed the basic surveys, and 54, 745 were evaluated to be at high risk of liver cancer. Of these high‐risk individuals, 40, 543 accepted the screening services. Determinants of participation for screening behavior included older age, being female, being positive for hepatitis B surface antigen, having a family history of liver cancer, chronic depression, and low income. The detection rate for liver cancer was estimated to be 0.41% (95% CI, 0.35–0.48). Conclusions: This study reported several significant factors associated with the screening behaviors for liver cancer. Lay Summary: Participation rate and results for liver cancer screening in rural areas are rarely reported. The determinants associated with adherence rates and early detection rate of liver cancer in an organized screening program for liver cancer were assessed. A possible positive correlation between the participation rates and the early detection rate was observed among attendees of screening. These new finds could be beneficial to increasing the participation rate of screening. Abstract : The participation rate for liver cancer screening is acceptable in a population‐based organized program for high‐risk individuals in rural areas. Factors associated with the participation rates have been determined.